2015
DOI: 10.1038/icb.2015.30
|View full text |Cite|
|
Sign up to set email alerts
|

Allergen‐induced interleukin‐18 promotes experimental eosinophilic oesophagitis in mice

Abstract: Elevated levels of IL-18 have been reported in a number of allergic diseases. We recently reported that IL-18 in the blood and IL-18Rα mRNA in the oesophagus are induced during human eosinophilic oesophagitis (EoE). Additionally, we earlier showed that iNKT cells are critical to EoE pathogenesis; however, the mechanism of iNKT cell activation in EoE is not well understood. Therefore, the current study focused on the hypothesis that allergen-induced IL-18 may have an important role in iNKT cell-mediated EoE pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Our early results showed increased levels of the IL-18 receptor transcript in humans [139]. We have recently demonstrated induction of IL-18 and its receptor in a mouse model of eosinophilic esophagitis (EoE) [91]. We have also demonstrated correlations between IL-18 and eosinophilia in human EoE patients in addition to the previously mentioned results of iNKT cells [90].…”
Section: Il-18-induced Allergic Diseasesmentioning
confidence: 77%
See 1 more Smart Citation
“…Our early results showed increased levels of the IL-18 receptor transcript in humans [139]. We have recently demonstrated induction of IL-18 and its receptor in a mouse model of eosinophilic esophagitis (EoE) [91]. We have also demonstrated correlations between IL-18 and eosinophilia in human EoE patients in addition to the previously mentioned results of iNKT cells [90].…”
Section: Il-18-induced Allergic Diseasesmentioning
confidence: 77%
“…The data from our group indicates that direct exposure of IL-18 to invariant NKT (iNKT) cells in vitro releases eosinophilia-promoting cytokines like IL-4, Il-5 and IL-13, and promotes eosinophilic inflammation in tissue [90]. Additionally, we showed that transgenic mice overexpressing IL-18 are capable of promoting pulmonary and gastrointestinal eosinophilic disorders presumably via this iNKT activation [91]. …”
Section: Role Of Il-18 In Allergic Diseasementioning
confidence: 99%
“…The Tulane Institutional Animal Care and Use Committee approved the animal protocols. Experimental EoE in mice was induced using methods described previously 3 , 4 , 5 that were used in accordance with National Institutes of Health guidelines. In brief, mice were lightly anesthetized with isoflurane (Iso-Flo; Abbott Laboratories, North Chicago, IL), and 100 μg of Aspergillus fumigatus (Greer Laboratories, Lenoir, NC) in 50 μL normal saline or 50 μL normal saline alone was given intranasally using a micropipette with the mouse held in the supine position 3 times/wk for 3 weeks.…”
Section: Supplementary Methodsmentioning
confidence: 99%
“…We previously reported that IL-18 induce iNKT cell activation to release the eosinophil activating cytokine IL-5, as IL-5-deficient mice and iNKT cell-deficient (CD1d null) mice do not induce EoE in response to intranasal IL-18 challenge. Thus allergen-induced IL-18 has a significant role in promoting IL-5 and iNKT dependent EoE pathogenesis in mice [102]. IL-18 overexpression induces Th1, Th2 cytokine-mediated airway inflammation in mice with an increase in IFNγ, IL-13, eotaxin levels and CD4 + T cells in ova sensitized mice [103].…”
Section: Role Of Il18 In Eosinophils Development and Maturitymentioning
confidence: 98%